Is ankle involvement underestimated in rheumatoid arthritis? Results of a multicenter ultrasound study - (:unkn) unknown (SPRINGER LONDON LTD, 2016)
The aim of this study is to investigate the prevalence of subclinical ankle involvement by ultrasound in patients with rheumatoid arthritis (RA). The study was conducted on 216 patients with RA and 200 healthy sex- and age-matched controls. Patients with no history or clinical evidence of ankle involvement underwent US examination. For each ankle, tibio-talar (TT) joint, tibialis anterior (TA) tendon, extensor halux (EH) and extensor common (EC) tendons, tibialis posterior (TP) tendon, flexor common (FC) tendon and flexor hallux (FH) tendon, peroneous brevis (PB) and longus (PL) tendons, Achilles tendon (AT) and plantar fascia (PF) were assessed. The following abnormalities were recorded: synovitis, tenosynovitis, bursitis, enthesopathy and rupture. BMI, DAS28, RF ESR and CRP were also obtained. A total of 432 ankles of patients with RA and 400 ankles of healthy controls were assessed. In 188 (87%) patients with RA, US showed ankle abnormalities whereas, in control group, US found abnormalities in 57 (28.5 %) subjects (p = 0.01). The most frequent US abnormality in RA patients was TP tenosynovits (69/216) (31.9 %), followed by PL tenosynovitis (58/216) (26.9 %), TT synovitis (54/216) (25 %), PB tenosynovitis (51/216) (23.6 %), AT enthesopathy (41/216) (19 %) and AT bursitis (22/216) (10.2 %). In 118 RA patients out of 216 (54.6%), a positive PD was found. No statistically significant correlation was found between the US findings and age, disease duration, BMI, DAS28, RF, ESR and CRP. The present study provides evidence of the higher prevalence of subclinical ankle involvement in RA patients than in age- and gender-matched healthy controls identified by US.
Keywords: Ankle; Rheumatoid arthritis; Subclinical involvement; Ultrasound; POWER DOPPLER ULTRASONOGRAPHY; CLINICAL EXAMINATION; MUSCULOSKELETAL ULTRASOUND; ANKYLOSING-SPONDYLITIS; PSORIATIC-ARTHRITIS; DISEASE-ACTIVITY; TENOSYNOVITIS; FOOT; ABNORMALITIES; ENTHESES